ANALISIS KINERJA KEUANGAN PERUSAHAAN DITINJAU DARI RASIO KEUANGAN DAN DU PONT SYSTEM (PT. UNILEVER INDONESIA PERIODE 2019-2022) - Patonah, Siti; Aisyah yulianti, Rini; Gunardi; Kesumah, Priatna (Jurnal Ekonomi Manajemen Bisnis Dan Akuntansi : EMBA, 2024)
The aim of this study was to evaluate Perseroan Terbatas Unilever Indonesia Terbuka's financial performance through time series and trend analysis, financial ratio analysis, and the Du Pont System. This study used documentation-sourced secondary data that was acquired from pertinent literature investigations, along with data gathering methodologies. Focusing on the balance sheet and income statement of Perseroan Terbatas Unilever Indonesia Terbuka's annual financial statements for the 2019–2022 period available on the business's official website.Financial ratio analysis, which computes the ratios for activity, profitability, liquidity, and leverage, reveals that the company's financial performance is weak except from variations. According to the Du Pont System results, the level of return on investment (the outcome of calculating net profit margin and total asset turnover) and the element of leverage have a major impact on the annual decline in the company's financial performance as measured by the achievement of return on equity.According to the research findings, the two analyses demonstrate that the firm's financial performance condition is poor and tends to fall from 2020 to 2022. This is because the company saw a decline in profits in early 2020 as a result of post-COVID-19 conditions. The aim of this study was to evaluate Perseroan Terbatas Unilever Indonesia Terbuka's financial performance through time series and trend analysis, financial ratio analysis, and the Du Pont System. This study used documentation-sourced secondary data that was acquired from pertinent literature investigations, along with data gathering methodologies. Focusing on the balance sheet and income statement of Perseroan Terbatas Unilever Indonesia Terbuka's annual financial statements for the 2019–2022 period available on the business's official website.Financial ratio analysis, which computes the ratios for activity, profitability, liquidity, and leverage, reveals that the company's financial performance is weak except from variations. According to the Du Pont System results, the level of return on investment (the outcome of calculating net profit margin and total asset turnover) and the element of leverage have a major impact on the annual decline in the company's financial performance as measured by the achievement of return on equity.According to the research findings, the two analyses demonstrate that the firm's financial performance condition is poor and tends to fall from 2020 to 2022. This is because the company saw a decline in profits in early 2020 as a result of post-COVID-19 conditions.